5S Method Usage for the Improvement of Production Process in the Manufacturing Company - Oleksiak Beata; Żyszczyński Maciej; Micor Klaudia (Management Systems in Production Engineering)
In the face of growing competition and dynamically changing market requirements, manufacturing companies are forced to continuously improve their processes, increase operational efficiency and reduce costs. The key factor enabling the achievement of these goals is the implementation of organizational tools supporting work optimization. The aim of this study was to analyze the possibilities of improving operational efficiency by applying the 5S methodology at selected work stations in a manufacturing company. The research was preceded by a diagnosis of the existing state, which revealed a number of irregularities in the organization of work stations and suboptimal use of work space. As a result of implementing the 5S method, including the stages of sorting, systematization, cleaning, standardization and self-discipline, measurable effects were obtained that improved the course of production processes. A significant reduction in the time of operation execution was observed – even by 40% – at the work stations covered by the implementation, as well as an improvement in work ergonomics, clarity of organizational rules and increased employee involvement in maintaining order. The obtained results confirm the validity and effectiveness of implementing lean management tools in production conditions.